Examples Of Accounting Manipulations Related To The Valuation Of Balance Sheet Components - Łojek, Paweł (Scientific Journal of Bielsko-Biala School of Finance and Law, 2021)
<!– [if gte mso 11]> <![endif]–> The concept of creative accounting is often mistakenly referred to as accounting manipulations in the field of valuation of the company’s assets, the possibility of concealing facts from the economic life of an individual, or as an attempted fraud (Jones 2011 and Stolowy, Breton 2000). Creativity should be assessed positively in the eyes of the recipients of financial statements and classified as a manifestation of in-depth knowledge of balance sheet law, tax law and, moreover, as the ability to apply the applicable normative acts. However, research conducted among professional accountants and statutory auditors in the period from September 2013 to February 2015 showed that only 20% of the respondents described creative accounting as a manifestation of the lack of data manipulation (Hołda, 2016).The aim of the article is to review the literature in the field of defining the concepts related to accounting manipulation and creative accounting. The study of the issue will present popular examples used in economic practice, which will be part of the empirical part and an attempt to evaluate the concepts by the author. The added value of the article is the possibility of developing research on the benefits of using creative accounting.<!– [if gte mso 11]> <![endif]–>